2013
DOI: 10.11646/zootaxa.3686.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovery of Biswamoyopterus (Mammalia: Rodentia: Sciuridae: Pteromyini) in Asia, with the description of a new species from Lao PDR

Abstract: A new species of the flying squirrel genus Biswamoyopterus is described from Lao PDR. It is based on a single specimen collected from a local food market at Ban Thongnami, Pak Kading District, Bolikhamxai Province. The new taxon shows close affinities to Biswamoyopterus biswasi, which is only known from the holotype collected in 1981, 1250 km from the current locality, in Arunachal Pradesh, Northeast India. However, it differs substantially in pelage colour, most particularly on the ventral surfaces of the bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 10 publications
(9 reference statements)
1
19
0
Order By: Relevance
“…, Sanamxay et al. ]). Traffic seizure data detail an increasing number of seizures in addition to a growth in seizure size since monitoring began in 1975 (TRAFFIC database: http://trade.cites.org/#).…”
Section: Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…, Sanamxay et al. ]). Traffic seizure data detail an increasing number of seizures in addition to a growth in seizure size since monitoring began in 1975 (TRAFFIC database: http://trade.cites.org/#).…”
Section: Issuesmentioning
confidence: 99%
“…Overview of hunting and trade.-Globally, the illegal wildlife trade is worth approximately $20 billion annually (South and Wyatt 2011), and in SE Asia, hunting and trade remain a major threat to biodiversity, despite moves to tighten regulations regarding international trade in endangered species. Bushmeat markets across the region still openly display various species, some of which are yet to be scientifically described (as evidenced by the Laotian rock rat, and Biswamoyopterus laoensis squirrel [Jenkins et al 2004, Sanamxay et al 2013). Traffic seizure data detail an increasing number of seizures in addition to a growth in seizure size since monitoring began in 1975 (TRAF-FIC database: http://trade.cites.org/#).…”
Section: Hunting and Tradementioning
confidence: 99%
“…These additions/modifications were necessary because over the past 10 years molecular and genetic techniques have evolved quickly and phylogenetic relationships between species have changed in many target groups (e.g. see Sanamxay et al 2013). We did not consider for our analysis the papers proposing new taxonomic arrangements still requiring investigation (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…1981 (specimen ZSI 20705) found in northeastern India, B. laoensis Sanamxay et al, 2013 (specimen NUoL FES. MM.12.163), found in central Laos, and B. gaoligongensis Li et al, 2019 (specimens ZSI 20705 & KIZ 034924), found in southwest China (Figure 2, see Saha 1981;Sanamxay et al 2013;Li et al 2019). No molecular data have been obtained about this genus so far.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2014, the Southeast Asia Biodiversity Research Institute, Chinese Academy of Sciences (CAS-SEABRI), has conducted several biodiversity expeditions to the northern Indo-China peninsula . This region is considered a globally important biodiversity hotspot for flora and fauna (Tordoff et al 2005), from where many species of mammals have been discovered or rediscovered since the 1990s (Amato et al 1999;Geissmann et al 2011;Sanamxay et al 2013;Fan et al 2017). In this work, using combined mitochondrial DNA and nuclear DNA loci, and morphological examination, we aim to revise the taxonomic status of the genus Biswamoyopterus and assess its phylogenetic position among flying squirrels.…”
Section: Introductionmentioning
confidence: 99%